Extracellular Vesicles Including Exosomes Regulate Innate Immune Responses to Hepatitis B Virus Infection - Kouwaki, Takahisa; Fukushima, Yoshimi; Daito, Takuji; Sanada, Takahiro; Yamamoto, Naoki; Mifsud, Edin J.; Leong, Chean Ring; Tsukiyama-Kohara, Kyoko; Kohara, Michinori; Matsumoto, Misako; Seya, Tsukasa; Oshiumi, Hiroyuki (Frontiers in Immunology, 2016)
The innate immune system is essential for controlling viral infection. Hepatitis B virus (HBV) persistently infects human hepatocytes and causes hepatocellular carcinoma. However, the innate immune response to HBV infection in vivo remains unclear. Using a tree shrew animal model, we showed that HBV infection induced hepatic interferon (IFN)-γ expression during early infection. Our in vitro study demonstrated that hepatic NK cells produced IFN-γ in response to HBV only in the presence of hepatic F4/80+ cells. Moreover, extracellular vesicles (EVs) released from HBV-infected hepatocytes contained viral nucleic acids and induced NKG2D ligand expression in macrophages by stimulating MyD88, TICAM-1, and MAVS-dependent pathways. In addition, depletion of exosomes from EVs markedly reduced NKG2D ligand expression, suggesting the importance of exosomes for NK cell activation. In contrast, infection of hepatocytes with HBV increased immunoregulatory microRNA levels in EVs and exosomes, which were transferred to macrophages, thereby suppressing IL-12p35 mRNA expression in macrophages to counteract the host innate immune response. IFN-γ increased the hepatic expression of DDX60 and augmented the DDX60-dependent degradation of cytoplasmic HBV RNA. Our results elucidated the crucial role of exosomes in antiviral innate immune response against HBV. Accession Number Accession number of RNA-seq data is DRA004164 (DRA in DDBJ).